Critical characteristics of an airlift pump for dredging - Hu, Dong; Guo, Jingzhi; Deng, Ling; Yang, Fengling (Frontiers in Earth Science, 2022)
Abstract: There are many factors that affect the airlift pump for dredging. In actual applications, if these factors cannot be fully considered, the performance of airlift pump will be reduced. In view of this, based on the critical model of water-solid two-phase flow and the gas holding model, a critical model of gas-water-solid three-phase flow is proposed. The research results show that, compared with two-phase flow, the critical water flow rate for lifting solids in three-phase flow is always smaller. Therefore, it is necessary to consider the static chip retention force so that the critical model in two-phase flow can be modified. It shows that the static chip retention effect is opposite to the "start" of the particle. Not only that, but also discussed the critical conditions of solid particles or vertical lifting water from a practical point of view. The results show that solid particles will not affect the critical air flow rate of pumping water. However, the size and location of the solid particles affect the critical air flow rate.